Nitric oxide for inhalation in ST-elevation myocardial infarction (NOMI): a multicentre, double-blind, randomized controlled trial. (24th May 2018) - Janssens, Stefan P; Bogaert, Jan; Zalewski, Jaroslaw; Toth, Attila; Adriaenssens, Tom; Belmans, Ann; Bennett, Johan; Claus, Piet; Desmet, Walter; Dubois, Christophe; Goetschalckx, Kaatje; Sinnaeve, Peter; et al.
Abstract: Aims: Inhalation of nitric oxide (iNO) during myocardial ischaemia and after reperfusion confers cardioprotection in preclinical studies via enhanced cyclic guanosine monophosphate (cGMP) signalling. We tested whether iNO reduces reperfusion injury in patients with ST-elevation myocardial infarction (STEMI; NCT01398384). Methods and results: We randomized in a double-blind, placebo-controlled study 250 STEMI patients to inhale oxygen with (iNO) or without (CON) 80 parts-per-million NO for 4 h following percutaneous revascularization. Primary efficacy endpoint was infarct size as a fraction of left ventricular (LV) size (IS/LVmass ), assessed by delayed enhancement contrast magnetic resonance imaging (MRI). Pre-specified subgroup analysis included thrombolysis-in-myocardial-infarction flow in the infarct-related artery, troponin T levels on admission, duration of symptoms, location of culprit lesion, and intra-arterial nitroglycerine (NTG) use. Secondary efficacy endpoints included IS relative to risk area (IS/AAR), myocardial salvage index, LV functional recovery, and clinical events at 4 and 12 months. In the overall population, IS/LVmass at 48–72 h was 18.0 ± 13.4% in iNO ( n = 109) and 19.4 ± 15.4% in CON [ n = 116, effect size −1.524 %, 95% confidence interval (95% CI) −5.28, 2.24; P = 0.427]. Subgroup analysis indicated consistency across clinical confounders of IS but significant treatment interaction with NTG ( P = 0.0093) resulting in smaller IS/LVmass after iNO in NTG-naïve patients ( n = 140, P < 0.05). The secondary endpoint IS/AAR was 53 ± 26% with iNO vs. 60 ± 26% in CON (effect size −6.8%, 95% CI −14.8, 1.3, P = 0.09) corresponding to a myocardial salvage index of 47 ± 26% vs. 40 ± 26%, respectively, P = 0.09. Cine-MRI showed similar LV volumes at 48–72 h, with a tendency towards smaller increases in end-systolic and end-diastolic volumes at 4 months in iNO ( P = 0.048 and P = 0.06, respectively, n = 197). Inhalation of nitric oxide was safe and significantly increased cGMP plasma levels during 4 h reperfusion. The Kaplan–Meier analysis for the composite of death, recurrent ischaemia, stroke, or rehospitalizations showed a tendency toward lower event rates with iNO at 4 months and 1 year (log-rank test P = 0.10 and P = 0.06, respectively). Conclusions: Inhalation of NO at 80 ppm for 4 h in STEMI was safe but did not reduce infarct size relative to absolute LVmass at 48–72h. The observed functional recovery and clinical event rates at follow-up and possible interaction with nitroglycerine warrant further studies of iNO in STEMI.